2015
DOI: 10.1016/j.atmosenv.2014.12.051
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo toxicity of urban and rural particulate matter from California

Abstract: Particulate matter (PM) varies in chemical composition and mass concentration based on location, source, and particle size. This study sought to evaluate the in vitro and in vivo toxicity of coarse (PM10-2.5) and fine (PM25) PM samples collected at 5 diverse sites within California. Coarse and fine PM samples were collected simultaneously at 2 rural and 3 urban sites within California during the summer. A human pulmonary microvascular endothelial cell line (HPMEC-ST1.6R) was exposed to PM suspensions (50 μg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Cell lines are representative of our target organ (lung), and were chosen because of their prevalence in the literature. These are robust models, widely used and described in the context of nanotoxicology (Foster et al, 1998;Chanput et al, 2014;Mirowsky et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Cell lines are representative of our target organ (lung), and were chosen because of their prevalence in the literature. These are robust models, widely used and described in the context of nanotoxicology (Foster et al, 1998;Chanput et al, 2014;Mirowsky et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, very few studies have identified the precise correlations between characteristics of seasonally variable PM2.5 and their effects on the respiratory and immune systems. The characteristics of ambient PM2.5 vary with location and season, and so do their effects (Mirowsky et al 2015). However, the contributing factors of PM2.5 for respiratory allergy and their biological responses have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of uncharacterized PM 2.5 hinders the ultimate goal of identifying key constituents responsible for health effects. Limited toxicology studies using filter-based extraction methods have characterized samples following partial or complete extraction procedures (Gerlofs-Nijland et al 2007; Jalava et al 2009; Huang et al 2014; Mirowsky et al 2015). These studies allow for connections to be made to components or groups of components in PM 2.5 that are the predominant factors in PM 2.5 -associated health outcomes.…”
Section: Discussionmentioning
confidence: 99%